Analytical study of the incidence of papillary carcinoma in thyroiditis cases and assessing the risk - V., Santhosh P.; M., Vinodh; V., Prasad R.; Augastine, Joy (International Journal of Research in Medical Sciences, 2016)
Background: The association between thyroid carcinoma and thyroiditis remains controversial in medical bibliography. Therefore, the present study was designed to investigate the incidence of papillary carcinoma in diagnosed cases of thyroiditis patients who underwent surgery and analyze the risk of carcinoma in thyroiditis patients. Methods: Patients of both sexes, age more than 13 with symptomatic thyroid swelling and diagnosed as any sub types of thyroiditis with FNAC/USG/Antibody titer in Government Medical College, Thrissur, India. 41females and 3 male patients were studied to assess risk of carcinoma in thyroiditis cases, analyzing the age, symptoms, clinical presentations and FNAC results. Results: 17 out of 44 cases showed post-operative biopsy as papillary carcinonoma.15 out of 17 papillary carcinoma cases diagnosed were above 36 years, with 6times increased risk, 95% CI = (1.142, 31.532). 10 out of 17 carcinoma cases have rapid increase in size (p=0.00). 82.4% of carcinoma cases have obstructive symptoms (p=0.00). FB sensation is more frequently seen in postoperative benign thyroiditis. 59% of the papillary carcinoma cases were diagnosed pre operatively as colloid with thyroiditis. Conclusions: Females aged more than 36years and all adult males with a rapid increase in size of the thyroid swelling and/or obstructive symptoms like dyspnoea/dysphagia, who’s FNAC suggestive of colloid with features of thyroiditis have a high malignant potential for papillary carcinoma, and total/near total thyroidectomy may be considered as an appropriate operative treatment.